Pengaruh Harga Dan Tempat Terhadap Omzet Penjualan Pada Usaha Manik-Manik Milik Ibu Rita Di Tenggarong - Abdullah, Rahim (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
From analysis data result and discussion, the regression equality which is resulted is Y = 0,727 + 0,293 X1 + 0,631 X2. This matter explain that there is same direction relation, it means if happen the increasing on X variable, so will cause the increasing to the Y variable. However constant value (a) as 0,727 explain if X1 andX2 same with zero, so the sale’s turnover same with 0,727 or can be said if there is no cost variable and place so the sale turnover is 0,727.Correlation which is resulted according to R number is 0,865, this matter point that correlation between cost and place with sale turnover is really strong, because 0,865 number is upper 0,5 and approach 1, r = 1.R square number is 0,749 comes from 0,8652, it means 74,9 % sale turnover can be explained or influenced by cost and place variable. However the rest ( 100 % - 74,9 % = 25,1 % ) sale turnover is explained or influenced by the another causes like promotion, model, desaign and so on.Anova experiment result r F test, is got F arithmetic as 87,843 with significance level 0,000. However F table value with df1 = 2 and df2 = 59, is got value as 3,150, it means that F arithmetic > F table or 87,843 > 3,150, so that can be said that cost and place variable together be able to show its influence to the sale turnover or regression model can be used to predict the sale turnover and the first hypothesis can be accepted. Key Word : Price, Place